Institutionalising maternal and newborn quality-of-care standards in Bangladesh, Ghana and Tanzania: a quasi-experimental study. Issue 9 (20th September 2022) - Manu, Alexander; Billah, Sk Massum; Williams, John; Kilima, Stella; Yeji, Francis; Matin, Ziaul; Hussein, Asia; Gohar, Fatima; Wobil, Priscilla; Baffoe, Peter; Karim, Farhana; Muganyizi, Projestine; et al.
Abstract : Introduction: Facility interventions to improve quality of care around childbirth are known but need to be packaged, tested and institutionalised within health systems to impact on maternal and newborn outcomes. Methods: We conducted cross-sectional assessments at baseline (2016) and after 18 months of provider-led implementation of UNICEF/WHO's Every Mother Every Newborn Quality Improvement (EMEN-QI) standards (preceding the WHO Standards for improving quality of maternal and newborn care in health facilities). 19 hospitals and health centres (2.8M catchment population) in Bangladesh, Ghana and Tanzania were involved and 24 from adjoining districts served for 'comparison'. We interviewed 43 facility managers and 818 providers, observed 1516 client–provider interactions, reviewed 12 020 records and exit-interviewed 1826 newly delivered women. We computed a 39-criteria institutionalisation score combining clinical, patient rights and cross-cutting domains from EMEN-QI and used routine/District Health Information System V.2 data to assess the impact on perinatal and maternal mortality. Results: EMEN-QI standards institutionalisation score increased from 61% to 80% during EMEN-QI implementation, exceeding 75% target. All mortality indicators showed a downward trajectory though not all reached statistical significance. Newborn case-fatality rate fell significantly by 25% in Bangladesh (RR=0·75 (95% CI=0·59 to 0·96), p=0·017) and 85% in Tanzania (RR=0.15 (95% CI=0.08 to 0.29), p<0.001), but not in Ghana. Similarly, stillbirth (RR=0.64 (95% CI=0.45 to 0.92), p<0.01) and perinatal mortality in Tanzania reduced significantly (RR=0.59 (95% CI=0.40 to 0.87), p=0.007). Institutional maternal mortality ratios generally reduced but were only significant in Ghana: 362/100 000 to 207/100 000 livebirths (RR=0.57 (95% CI=0.33 to 0.99), p=0.046). Routine mortality data from comparison facilities were limited and scarce. Systematic death audits and clinical mentorship drove these achievements but challenges still remain around human resource management and equipment maintenance systems. Conclusion: Institutionalisation of the UNICEF/WHO EMEN-QI standards as a package is feasible within existing health systems and may reduce mortality around childbirth. Critical gaps around sustainability must be fundamental considerations for scale-up.